2010
DOI: 10.1021/ja106637e
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Suppression of Melanoma Cells by Inducible DNA Cross-Linking Agents: Bis(catechol) Derivatives

Abstract: A series of bis(catechol) quaternary ammonium derivatives were designed and synthesized. We investigated their ability to cross-link DNA induced by tyrosinase and found that the o-quinone is key intermediate in the process by using the nucleophile 3-methyl-2-benzothiazolinone hydrazone (MBTH) in the tyrosinase assay. Their cytotoxicities to B16F1, Hela, and CHO cells were tested by MTT assays. The specific and potent abilities to kill the tyrosinase-efficient melanoma cells kindled our interest in exploring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Taken together, these results imply that ortho-quinone plays an important role in not only antioxidant, but also prooxidant action, of catechol type compounds. From an antioxidant point of view, this prooxidant action is a drawback, but the prooxidant-induced DNA strand breakage is believed to be a promising strategy for killing cancer cells (Bai et al, 2010;Fan et al, 2009). Zhou and co-workers have recently reported that bis(catechol) derivatives could selectively suppress melanoma cells by inducing DNA cross-link via an ortho-quinone intermediate (Bai et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results imply that ortho-quinone plays an important role in not only antioxidant, but also prooxidant action, of catechol type compounds. From an antioxidant point of view, this prooxidant action is a drawback, but the prooxidant-induced DNA strand breakage is believed to be a promising strategy for killing cancer cells (Bai et al, 2010;Fan et al, 2009). Zhou and co-workers have recently reported that bis(catechol) derivatives could selectively suppress melanoma cells by inducing DNA cross-link via an ortho-quinone intermediate (Bai et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Due to frangibility, reactions of nucleic acids were required to be very mild, selective and readily controllable. o -Quinone intermediate, an actively potent DNA cross-linking unit resulted from a catechol precursor upon oxidation, has been proved to possess good cross-linking activity toward duplex DNAs without resulting in G-quadruplex cross-linked25. A superiority of the o -quinone mediated DNA cross-linking was that it could be readily stimulated by tyrosinase, which is highly expressed in some malignant tumors26272829, thus bringing in good cell selectivity.…”
mentioning
confidence: 99%
“…Taken together, the catechol moiety was an ideal scaffold that could fit multifaceted requirements. We previously reported N,N′-(3,4-Dihydroxylbenzyl)-N,N,N′,N′–tetramethyl-4,4′-biphenyldiamine dibromide as double strand DNA cross-linking agent25. In these studies, for purpose of demonstration of G-quadruplex's existence in vivo , we designed a new series of Schiff-base catechol derivatives as G-quadruplex cross-linking candidates.…”
mentioning
confidence: 99%
“…Catechol was recently used in the selective modification of DNA in cancer cells. [29] Catechol, with a 1,2-diol, also shows a decreased IC 50 value of 71 mm. We synthesized a derivative that is not prone to oxidation: An-Hq-CH 3 .…”
Section: Reaction With 2'-deoxyguanosinementioning
confidence: 95%